Dried Date Juice on Hemoglobin and Blood Glucose Levels in Pregnant Women at The Community Health Centre in Bogor Region - Sari, Novita; Febry Mutiariami Dahlan; Putri Azzahroh (Rajaki of Tulip Medika Publisher, 2025)
Background: The second highest MMR in Indonesia in 2023 was due to obstetric haemorrhage, which accounted for 17.16% of the total MMR of 4,129. One of the factors causing obstetric haemorrhage is anaemia. In 2023, the Indonesian Health Service Office reported that the proportion of anaemia in pregnant women in Indonesia was 27.7%, and in West Java in 2023 it was 10.44%. One of the non-pharmacological therapies to help overcome anaemia is the administration of date juice. Purpose: This study aims to determine the effect of date juice administration on haemoglobin levels and blood glucose levels in pregnant women with anaemia. Method: This type of research is a pre-experimental one-group pretest-posttest design. The population is pregnant women in the third trimester with anaemia. The sample in this study consisted of 20 people who were then given treatment. The sampling technique used purposive sampling. Bivariate analysis used the Wilcoxon test and Paired sample t test. Result: The results showed an increase in the average haemoglobin level before (10.11 g/dL) and after (11.60 g/dL) the providing of date juice. Meanwhile, the average blood glucose level before (96.30 mg/dL) and after (96.65 mg/dL) showed a slight increase. The results of the Wolcoxon test on haemoglobin levels showed a p value = 0.000, so there is a significant effect of date juice administration on haemoglobin levels. Meanwhile, from the results of the paired sample t test on blood glucose levels, the p value = 0.953, so there is no effect of date juice administration on blood glucose levels in pregnant women in the third trimester with anaemia. Conclusion: There is an effect of date juice on increasing haemoglobin levels and no effect on blood glucose levels in pregnant women in their third trimester with anaemia.